The Digitization of Notarial Tasks - A Comparative Overview and Outlook of ‘Cyber Notary’ In Indonesia and Germany - Koos, Stefan (The Indonesian Journal of Socio-Legal Studies, 2023)
This article highlights the newer discussion of the term "cyber notary" in the Indonesian legal context and compares the discussion with the discussion on the use of digital instruments for German notaries. The article notes that the concept of cyber notary is being discussed in Germany and other EU-member states as well, where the integration of digital and cyber elements into the notary system is considered as a way to make processes more efficient, accessible, and secure. This includes the use of digital signatures, online notarization, the use of notarial blockchains, or secure digital storage for notarized documents. However, the implementation of cyber notary systems in Indonesia is still in a very early stage and not yet fully regulated. Consequently, it needs more discussion for the consistent integration of digital instruments for notarial work into the legal system of Indonesia. The article provides a comprehensive overview of the situation of the digitalization of notarial tasks in Indonesia. It presents some new developments in Germany that are relevant for cyber notaries and may be interesting for the development of digitalization of notarial work processes in Indonesia. Finally, the article will discuss some aspects of the ongoing digitalization that may affect the profession of notaries in the future. As in all legal professions, we are facing future disruptive developments through digitalization, namely with artificial intelligence, blockchain technology, or cloud computing. The article aims to show that AI and blockchain technology will not replace civil law notaries in the near and middle term but will be integrated into the daily work of notaries as supporting instruments.